Improved exosome isolation methods from non-small lung cancer cells (NC1975) and their characterization using morphological and surface protein biomarker methods - Elham O. Mahgoub (17707221) (2023)
This study has demonstrated improved methods for isolating exosomes from non-small lung cancer cells, which address the problems characterized by exosome morphological and chemical methods. To improve the isolation methods, cells from the NCI 1975 cell line were used as the source for exosomes. The isolation processes were carried out using serial isolation techniques in addition to specific preservation tools. The isolated exosomes were characterized using transmission electron microscopy (TEM), and scanning electron microscopy (SEM) was added for further assurance of the investigation results. The statistical analysis results showed that the size distributions of apoptotic vesicles (APV) 450 nm and necrotic bodies (NCB) 280 nm (extracellular vesicles) were significantly different from exosomes (P < 0.001). In contrast, the exosome size distribution was not significantly different from the published exosome sizes, as demonstrated by statistical analysis tools. This study confirmed the improved methods for isolating exosomes that make exosomes accessible for use in the diagnosis and prognosis of non-small cell lung cancer (NSCLC). Other Information Published in: Journal of Cancer Research and Clinical Oncology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00432-023-04682-6